Population ecology of small mammals in forest ecosystems (Zoological Records and Reviews, 2023)
Small mammals -- rodents, shrews, and insectivores occupying forest floor, understorey, and canopy niches -- arekeystone components of forest ecosystems, functioning simultaneously as herbivores, seed dispersers, mycorrhizalinoculants, insectivores, and prey for mesopredators and raptors. Their population dynamics -- characterised bymulti-annual cycles driven by food availability, predation pressure, and density-dependent regulation -- have cascadingeffects on forest regeneration, arthropod community composition, and predator-prey dynamics across multiple trophiclevels. This review synthesises evidence from 188 primary studies (2005-2023) examining the population ecology ofsmall mammals in European forest ecosystems, evaluating population dynamics, habitat associations, interspecificinteractions, and responses to forest management and climate variability across boreal, temperate, and Mediterraneanforest types. Masting events -- synchronised mass seed production by beech and oak -- drive 2-4 year population cyclesin Apodemus flavicollis and Myodes glareolus, with peak densities reaching 80-140 individuals per hectare following mastyears and crashes to < 5 per hectare in subsequent mast failures. Forest management intensity significantly affects smallmammal diversity: naturally structured forests with high deadwood volume and canopy heterogeneity support 2.4-foldhigher small mammal species richness than intensively managed even-aged plantations. Climate variability -- particularlydrought effects on mast production and the synchrony of masting across Europe -- is emerging as a key driver ofrange-wide population dynamics. Conservation implications for forest management certification, raptor conservation, andtick-borne disease risk management are discussed.
Keywords: raptor prey base; seed dispersal; forest management; rodent cycles; Myodes glareolus; Apodemus; masting; population dynamics; forest ecology; small mammals